Motion Videocapture and Treadmill to study Postural Reactivity and Transition: Application to the condition of Dry Immersion in Parkinson's Disease - Alexander Meigal (FRUCT, 2021)
The purpose of this study was to evaluate technical reliability of a commercially available treadmill to induce slip displacement, which is sufficient to provoke postural reactivity in subjects with Parkinson's disease (PD). These subjects underwent the program of ground-based microgravity modeled with ""dry"" immersion (DI). Additionally, in the same study group we assessed the function of postural transition. Both postural reactivity and transition were traced with motion videocapture technique. We found, that at 1 km/hour treadmill did produce acceleration, and, hence heel strike, detectable for motion videocapture. Therefore, from the methodological point of view the study looks promising. However, this acceleration proved 3-4 time lesser than it is usually applied in suchlike studies. In part, this explains for the lack of significant effect of the DI program on the characteristics of postural compensation reactions in subjects with PD. Alternatively, the result could be explained by weak effect of DI on the studied postural functions. For future studies, we regard that inertial measuring units (IMU) and stronger acceleration would better fit the task to study postural reactions in subjects with PD.